PENGARUH PEMBERIAN EKSTRAK DAUN DELIMA (PUNICA GRANATUM L.) DALAM PENGOBATAN IKAN KERAPU CANTANG (EPINEPHELUS SP.) YANG TERSERANG VIBRIO ALGINOLYTICUS - Marselina Fangidae; Yuliana Saloso; Cindy Soewarlan (Nusa Cendana University, 2018)
Abtract - This research aims to prevent, the effect of pomegranate extract in the treatment of Cantang grouper and the concentration of pomegranate extract which is appropriate to the survival rate of Cantang (Epinephelus sp) infected by V. alginolitycus. The method of this research is laboratory experiment using three treatments and each treatment is done by three replications, 5%, 10% and 15% of pomegranate extract concentration is done in BBIP Tablolong, Kupang Barat subdistrict, Kupang regency. The indicator used to determine the effectiveness of pomegranate extract is by measuring the haemotology and morphology of fish while the indicator to see the exact concentration of extract is to see the test fish synthesis. The results showed that giving of pomegranate extract had an effect on V. alginolitycus and treatment with concentration of extract 10% showed higher survival than other treatment. Keyword: Pomegranate extrack, V. alginolitycus, Treatment, Cantang grouper